2014
DOI: 10.1186/s13058-014-0436-4
|View full text |Cite
|
Sign up to set email alerts
|

The forkhead transcription factor FOXM1 promotes endocrine resistance and invasiveness in estrogen receptor-positive breast cancer by expansion of stem-like cancer cells

Abstract: IntroductionThe forkhead transcription factor FOXM1 coordinates expression of cell cycle-related genes and plays a pivotal role in tumorigenesis and cancer progression. We previously showed that FOXM1 acts downstream of 14-3-3ζ signaling, the elevation of which correlates with a more aggressive tumor phenotype. However, the role that FOXM1 might play in engendering resistance to endocrine treatments in estrogen receptor-positive (ER+) patients when tumor FOXM1 is high has not been clearly defined yet.MethodsWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
123
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 66 publications
2
123
0
Order By: Relevance
“…We found FOXM1 to be expressed in 94% of the tumors and highly expressed in 37% of cases. Interestingly, these results show that FOXM1 is more expressed in male than in female breast cancer, since previous studies demonstrated that 87% of female breast tumors express FOXM1 and 20% of these were classified as high-expression [26,27]. This confirms the aggressive phenotype of male breast cancer.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We found FOXM1 to be expressed in 94% of the tumors and highly expressed in 37% of cases. Interestingly, these results show that FOXM1 is more expressed in male than in female breast cancer, since previous studies demonstrated that 87% of female breast tumors express FOXM1 and 20% of these were classified as high-expression [26,27]. This confirms the aggressive phenotype of male breast cancer.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, many studies demonstrated that FOXM1 contributes to all hallmarks of cancer [19,20], which explains the numerous emerging studies indicating FOXM1 as an important target for cancer therapy in the near future that offers exciting prospects [21][22][23][24]. Overexpression of FOXM1 has been reported in a large variety of human cancers including female breast cancer [25][26][27], and it correlated with tumor progression and poor prognosis [28]. However, the prognostic value of FOXM1 overexpression in male breast cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…FOXM1 is a dynamic cancer-associated biomarker involved in the regulation of various biological processes, including cell cycle progression, differentiation, metastasis, invasion and angiogenesis (14)(15)(16)(17)(18). In a previous study, the present authors demonstrated that FOXM1 was overexpressed in cervical cancer tissues, and its nuclear expression was observed to be correlated with the pathological grade of the tumor (19).…”
Section: Introductionmentioning
confidence: 66%
“…The role of FOX proteins in various types of cancer has been comprehensively investigated considering that these proteins have vital functions on biological processes. Certain Fox members including FOXP1, FOXM1, FOXR1 and FOXA1, show a diversity of activities on tumorigenesis and progression of cancer (4)(5)(6)(7)(8), while having dual roles in cancer biology. For instance, on the one hand, FOXP1 overexpression by chromosome translocations is associated with poor prognosis in lymphomas, suggesting it acts as an oncogene (4).…”
Section: Introductionmentioning
confidence: 99%